Nutrigenomic activity of plant derived compounds in health and disease: Results of a dietary intervention study in dog. (December 2016) - Sgorlon, Sandy; Stefanon, Bruno; Sandri, Misa; Colitti, Monica
Abstract: The study was conducted to investigate the effects of dietary administrations of four nutraceuticals in dogs. Seventy four dogs were enrolled in the trials, 24 healthy dogs were fed with a control diet (CT) and the experimental groups received for 60 days the same diet supplemented with nutraceuticals, namely Echinacea angustifolia (EA, 0.10 mg/kg live weight as echinacoside; 14 dogs), Vaccinium myrtillus (VM, 0.20 mg/kg live weight as anthocyanidin, 13 dogs), Curcuma longa (CL, 6.60 mg/kg live weight as curcumin, 18 dogs with arthrosis), and Sylibum marianum (SM, 1.5 mg/kg live weight as sylibin, 8 dogs with hepatopathy). Dogs were weighted at the beginning of study and blood samples were collected at the beginning (T0) and at the end (T60) of the study. VM significantly down regulated TNF, CXCL8, NFKB1 and PTGS2 and decreased plasma ceruloplasmin (CuCp). The activity of EA was evidenced by the significant decrease of TNF and NFKB1 expression and CuCp levels and by the increase of plasma Zn. Administration of CL caused a significant decrease of CuCp and increase of Zn and a down regulation of TNF, CXCL8, NFKB1 and PTGS2, corroborating the anti-inflammatory action of curcuminoids. After 60 days of treatment with SM, plasma ALT/GPT activity was reduced and paraoxonase was increased, supporting the antioxidant activity of silymarin, also confirmed by the significant up regulation of SOD2 . Results indicated that nutraceutical administrations in dogs can be an interesting approach to modulate immune response in order to improve health condition of animals. Highlights: Functional compounds modulate physiological response in dogs. Curcuma longa extract down regulated the main pro inflammatory cytokines. Vaccinium myrtillus extract demonstrated anti-inflammatory and antioxidant activities. Echinacea angustifolia extract showed an immunomodulatory activity. Sylibum marianum confirmed antioxidant and liver protectant activities.